2015
DOI: 10.1007/s00429-015-0995-x
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary exercise induces neurogenesis in the hypothalamus and ependymal lining of the third ventricle

Abstract: In the adult hypothalamus and ependymal lining of the third ventricle, tanycytes function as multipotential progenitor cells that enable continuous neurogenesis, suggesting that tanycytes may be able to mediate the restoration of homeostatic function after stroke. Voluntary wheel running has been shown to alter neurochemistry and neuronal function and to increase neurogenesis in rodents. In the present study, we found that voluntary exercise improved the survival rate and energy balance of stroke-prone spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 39 publications
0
32
0
1
Order By: Relevance
“…) and in the hypothalamus (Niwa et al . ). These anatomically widespread increases in adult neurogenesis in response to sustained aerobic exercise suggest that in addition to mechanisms local to the hippocampus, such as increased androgenic function (Okamoto et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and in the hypothalamus (Niwa et al . ). These anatomically widespread increases in adult neurogenesis in response to sustained aerobic exercise suggest that in addition to mechanisms local to the hippocampus, such as increased androgenic function (Okamoto et al .…”
Section: Discussionmentioning
confidence: 97%
“…) and in the hypothalamus (Niwa et al . ), suggesting that the neurogenic effect of exercise might occur throughout the brain.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported the incorporation of BrdU by cells in the brain parenchyma surrounding the 3rdV. Most studies, however, did not distinguish between the ependymal cell layer in the 3rdV and the hypothalamic parenchyma, and thus did not examine the ependymal cell layer independently of the neighbouring brain parenchyma (Chouaf-Lakhdar et al, 2003;Ernst & Christie, 2005;Kokoeva et al, 2005Kokoeva et al, , 2007Xu et al, 2005;Bennett et al, 2009;Matsuzaki et al, 2009;Pierce & Xu, 2010;Niwa et al, 2016). Although not quantified, the images presented in these reports suggest limited cell proliferation in the ependymal layer, but the extent of the proliferation appears to vary considerably in these studies.…”
Section: In Vivo Proliferation Of Cells In Brain Parenchyma Adjacent mentioning
confidence: 99%
“…Changes in metabolic conditions can also modify the proliferation of hypothalamic neuronal precursors (Table 1), including high temperatures (Matsuzaki et al, 2009), physical activity (Niwa et al, 2016), and a high fat diet (HFD) (Kokoeva et al, 2005; Lee and Blackshaw, 2012; GouazĂ© et al, 2013; Nascimento et al, 2016). During prenatal neurogenesis, in utero exposure to a HFD stimulates the production of orexigenic hypothalamic neurons (Chang et al, 2008), which causes changes in behavior and physiological conditions that extend into adulthood as demonstrated by the increased body weight and caloric intake observed in P70 (Chang et al, 2008).…”
Section: Hypothalamic Neurogenesis As An Adaptive Metabolic Mechanismmentioning
confidence: 99%